Development Of Argumentation-Based 3D Audio Visual Media Exploding Box To Improve Students' Critical Thinking In Elementary Schools - Fajar Agus Agus Hari Firmansyah; Waspodo Tjipto Subroto; Hendratno Hendratno (Lembaga Pengembangan Kinerja Dosen, 2023)
Abstract consist of the background of the problem, The results of the interviews also explained that teachers had difficulty making teaching aids or learning media so that they experienced obstacles in providing material to students. Based on the background of the problem and needs analysis, the formulation of the problem is the validity of Exploding Box 3D Audio Visual media, practicality of Exploding Box 3D Audio Visual media, Effectiveness of Exploding Box 3D Audio Visual media. Based on data analysis and discussion of research results, then associated with the formulation of the problem and research objectives, it was concluded that the validation of the media developed by the researchers received an assessment of 94%, meaning that the reliability of the media obtained results worthy of slight revisions. Validation of the material developed by researchers received an assessment reaches 89%, meaning that the reliability of the material in the media gets decent results with a little revision, the practicality validation of the media developed by researchers gets an assessment from the teacher validator reaches 95%, it means that the practicality reliability of the media gets decent results with a little revision, the practical validation of the media developed by researchers gets an assessment From the responses of the students, it was obtained that the percentage mode was ≥ 80% with the category suitable for use. Validation of the effectiveness of the media developed by researchers. From the 10 questionnaire statements, the mode percentage was obtained ≥ 90% with the category suitable for use, and the results of critical thinking test questions from the pretest value of 54% with the value of the increase in the posttest from the value of 95%. Therefore it can be concluded that the pretest data for students' critical thinking skills is very good because they have reached the specified KKM